Mormonisme et migration : la religion comme “amortisseur” des processus migratoires transatlantiques - Eliott Mourier (Les Cahiers ALHIM)
Commanded by prophetical decree in its beginnings and today admitted as an endemically unavoidable phenomenon (although officially not recommended by its hierarchy), migrations are a key element in the understanding of Mormonism and more widely, of transnational religious organizations. Mormonism, with its legacy of historical migrations, offers a very interesting case study for the scientific analysis of the relationship between migration and religion. Such a relationship that seems “complementary” to our judgement for several reasons. First, because those religious movements have historically taken, and will indeed take advantage of those migratory flows in order to maintain their vitality, and then, because it is clear that those transnational religions can provide their members with a “ security net ” that will cushion the shocks recurrent all along the different steps of the migratory process.